Gold vis-à-vis money in Islam: the case against Dinarist movement - Mohamad, Azhar; Mohammad Sifat, Imtiaz (Emerald Group Publishing Ltd., 2017)
This paper delves in an aspect of monetary economics, addressing its Islamic wing in general and dinar advocates in particular. It argues that calls to reinstitution of dinar currencies are not only anachronistic and unnecessary, but also counter-productive and potentially unislamic. It further posits that regardless of nature of economy, legal tender fiat money and bank money are of same genus and treating them otherwise isn’t consistent with Islamic jurisprudential precepts. We also highlight that mismanagement, avarice, and human follies are to blame for financial maladies; regression to metallic currency is neither a panacea to the conundrums nor Islamic.